Hubungan Power Tungkai Dan Power Lengan Terhadap Jumping Smash Siswa Ekstrakulikuler Badminton Ma Nurul Falah - Ziqri Yahandi; Widati Amalin Ulfah; Ivandi Rahman; Chopa Renaldi; Artha Yuranda; Muhammad Irfan Saputra (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
This study aims to determine the contribution of leg power and arm power to jumping smash in badminton extracurricular students at MA Nurul Falah Airmesu Timur. The problem in this study is